2000
DOI: 10.1002/1098-2388(200007/08)19:1<54::aid-ssu9>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Second-look and second surgery: Second chance or second best?

Abstract: About 40 years ago, second‐look laparotomy (SLL) was introduced to evaluate, surgically and pathologically, primary treatment in case a clinical complete remission was obtained in ovarian cancer patients. But does SLL increase the disease‐free or overall survival? Important technical aspects of the procedure as: how many biopsies should be taken, can lapraoscopy be replaced by laparotomy and should complete lymphadnectomy be performed at SLL, are still not clarified. This and maybe even more important issues, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 42 publications
0
8
0
2
Order By: Relevance
“…[9][10][11] Also, many parameters have been reported to correlate with the result of SLL, such as stage, histologic subtype, differentiation, age of the patient, and residual disease after the first cytoreductive operation. 5,20 In the present study, there were only two cases of positive SLL findings among 30 patients with early-stage ovarian cancer who received SLL (6.7%). Several authors have reported higher rates of positive SLL findings, ranging between 14% and 26%, in early-stage patients.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…[9][10][11] Also, many parameters have been reported to correlate with the result of SLL, such as stage, histologic subtype, differentiation, age of the patient, and residual disease after the first cytoreductive operation. 5,20 In the present study, there were only two cases of positive SLL findings among 30 patients with early-stage ovarian cancer who received SLL (6.7%). Several authors have reported higher rates of positive SLL findings, ranging between 14% and 26%, in early-stage patients.…”
Section: Discussionmentioning
confidence: 46%
“…5,17,18 Some authors have reported that SLL has a positive effect on the survival of the patients, 6,19 although many others claimed that SLL did not increase the disease-free or overall survival. [9][10][11] Also, many parameters have been reported to correlate with the result of SLL, such as stage, histologic subtype, differentiation, age of the patient, and residual disease after the first cytoreductive operation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Trente-cinq pour cent des patientes sans lésion macroscopique ou microscopique retrouvée lors de la laparotomie de réévaluation ont développé une récidive dans l'année suivant le geste chirurgical, d'après l'étude de Sijmons et Heintz [34]. En fait, lors de cette intervention, l'éva-luation exacte de la maladie résiduelle peut être difficile du fait des remaniements secondaires à la première intervention chirurgicale, et des lésions de petite taille non visibles par le chirurgien peuvent être laissées en place.…”
Section: Cancer De L'ovaireunclassified